1998
DOI: 10.1007/bf03012105
|View full text |Cite
|
Sign up to set email alerts
|

Severe interactions with classic and selective monoamine oxidase inhibitors

Abstract: Oculocardiac reflex-peHbulbar block or opioid-relaxant anaesthesiaTo the Editor: The Oculocardiac reflex (OCR) can be induced by traction on the extraocular muscles. It usually manifests as bradycardia, nodal rhythm, ectopic beats, ventricular fibrillation and asystole. The reported incidence of OCR during general anaesthesia (GA) varies from 56 -67%. 1,5 This study was designed to compare the effects of peribulbar block (LA) and opioid-relaxant anaesthesia on the incidence of OCR in 30 patients undergoing sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Anticholinergic agents used include glycopyrrolate and atropine, neither of which should adversely interact with MAOIs, although there are 2 reports of severe hypertensive reactions and arrhythmias in patients tak- ing MAOIs (one taking phenelzine and one taking selegiline) who both received ephedrine and atropine. 16 Presumably, the patients' adverse reactions were from the combination of the MAOI and the ephedrine, but the fact that both patients received atropine confounds the issue. In a review of MAOI and elective surgery, 47 patients received atropine as a premedication without any untoward effect.…”
Section: Discussionmentioning
confidence: 98%
“…Anticholinergic agents used include glycopyrrolate and atropine, neither of which should adversely interact with MAOIs, although there are 2 reports of severe hypertensive reactions and arrhythmias in patients tak- ing MAOIs (one taking phenelzine and one taking selegiline) who both received ephedrine and atropine. 16 Presumably, the patients' adverse reactions were from the combination of the MAOI and the ephedrine, but the fact that both patients received atropine confounds the issue. In a review of MAOI and elective surgery, 47 patients received atropine as a premedication without any untoward effect.…”
Section: Discussionmentioning
confidence: 98%
“…Phenylephrine was used by other therapists for perioperative hypotension in epidural anesthesia [19,30], however, it was suggested that phenylephrine exhibits partly indirect sympathomimetic activity and may be better substituted by norepinephrine [29]. An interaction of phenelzine and selegilin with indirect sympathomimetic ephedrine was reported for spinal anesthesia with blood pressure of 245/125 mmHg and 240/120 mmHg, respectively [45]. In contrast, moclobemide and ephedrine did not yield an interaction in one patient [30].…”
Section: Case Report With Discussionmentioning
confidence: 99%
“…For example, a 21‐year‐old on an MAOI, developed hypotension and bradycardia while under spinal anaesthesia. This was treated with ephedrine and atropine but she subsequently developed agitation, dyspnoea, severe headache, hypertension and tachycardia [2]. Churchill‐Davidson advised checking patients' sensitivity to MAOIs and opioids by giving a test dose of 5 mg of pethidine and monitoring vital signs regularly [3].…”
mentioning
confidence: 99%